Enacting the Bible in medieval and early modern drama - Contzen, Eva von; Goodblatt, Chanita (Manchester University Press, 2020)
The thirteen chapters in this collection open up new horizons for the study of biblical drama by putting special emphasis on multitemporality, the intersections of biblical narrative and performance, and the strategies employed by playwrights to rework and adapt the biblical source material in Catholic, Protestant and Jewish culture. Aspects under scrutiny include dramatic traditions, confessional and religious rites, dogmas and debates, conceptualisations of performance, and audience response. The contributors stress the co-presence of biblical and contemporary concerns in the periods under discussion, conceiving of biblical drama as a central participant in the dynamic struggle to both interpret and translate the Bible.